Evaluation of the Cepheid Xpert MTB/RIF assay. (January 2015) - Shinnick, Thomas M; Starks, Angela M; Alexander, Heather L; Castro, Kenneth G
<x xml:space="preserve">Abstract</x> The lack of capacity to provide laboratory confirmation of a diagnosis of tuberculosis disease (TB) is contributing to enormous gaps in the ability to find, treat and follow TB patients. WHO estimates that globally only about 57% of the notified new cases of pulmonary TB in 2012 and about 19% of rifampicin-resistant TB cases were laboratory confirmed. The Cepheid Xpert® MTB/RIF assay has been credited with revolutionizing laboratory testing to aid in the diagnosis of TB and rifampicin-resistant TB. This semi-automated test can detect both the causative agent of TB and mutations that confer rifampicin resistance from clinical specimens within 2 h after starting the test. In this article, we review the performance of the test, its pathway to regulatory approval and endorsement, guidelines for its use and lessons learned from the implementation of the test in low-burden, high-resource countries and in high-burden, low-resource countries.